Retracted: RELASI KUASA DAN BISNIS - MARCUS FRETS PESSIRERON; Justintje A. Moriolkosu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2020)
https://bit.ly/SuratPermohonanPencabutanArtikelThis study aims to obtain in depth information about the pattern of relations between ruling groups and entrepreneurs in the maros political atmosphere in Indonesia.  This type of research is qualitative by using a constructivism approach. In collecting data researchers gather discourse data through print and electronic media and researchers act always as research instruments. Collected data is the relationship between the authorities and entrepreneurs in the Maros political atmosphere in Indonesia. In data collection, researchers collected, discourse data through print and electronic media and researchers acted as instruments of research. Data collected was the relationship between rulers and entrepreneurs in the political atmosphere of Maros in Indonesia. This data was obtained through two sources namely documentation and informants. Collection techniques the data was carried out through the in depth interview method. Furthermore, the data was analyzed using interactive analysis techniques intended to see the process of meaning and effects of discourse production and reproduction. The results showed that power relations between ruling groups and entrepreneurial groups had two objective and subjective dimensions reciprocally influential in producing up to reproducing the discourse of power it produces support for upper level middle level ruling groups to the lowest level of authority in the region.